Rachunek odchyleń w rachunku kosztów standardowych - Kes, Zdzisław (Analysis of Deviation in Standard's Cost Account, 2005)
It present elements of classifications of systems of cost account ¡n article. It present basic methods of analysis of deviations with use of standard cost account. It concentrates on discussion of subsequent difference from application of variable and full standard cost account.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 218-226